Analisis Penerapan Sistem Kerja Kontrak Karyawan pada PT NGK Busi Indonesia - Sri Isnaeni Achmad; Syamsurizal Syamsurizal; Anwar Mustofa (Administratif Profesional, 2020)
This study aims to determine whether the implementation of the contract work system at PT NGK Busi Indonesia is in accordance with Law No. 13 of 2003 on Manpower. This research is qualitative descriptive. Data were collected using 3 methods, namely in-depth interviews, observation and documentation. Data interpretation is done in stages starting from data collection, data reduction, until the final conclusions are obtained. The results showed that the implementation of the contract work system at PT NGK Busi Indonesia was in accordance with the Manpower Law. There are 6 indicators namely Job Training, Work Agreement, Protection, Wages, Welfare, and Termination of Employment. Employees are given training for 3 months before the contract period, the term of the work agreement for 1 year and can be extended 1 time with a period of 1 year as well. Employees get social security, health benefits, transportation, and food. They also get paid leave and overtime pay. The wage system uses the Provincial Sectoral Minimum Wage.